Exposure to biodiesel exhaust is less harmful than exposure to mineral diesel exhaust on blood-brain barrier integrity in a murine model - Nesbit, Michael; Ko, Colleen Kah Ling; Mamo, John C. L.; Lam, Virginie; Landwehr, Katherine R.; Larcombe, Alexander N.; Takechi, Ryu (Frontiers in Neuroscience, 2024)
Emerging data suggest that air pollution is a persistent source of neuroinflammation, reactive oxygen species (ROS), and neuropathology that contributes to central nervous system (CNS) disorders. Previous research using animal models has shown that exposure to diesel exhaust causes considerable disruption of the blood-brain barrier (BBB), leading to marked neuroinflammation. However, the effects of biodiesel exhaust on cerebrovascular integrity and neuroinflammation have not been explored previously. Therefore, in this study, 8-week-old BALB/c mice were exposed to biodiesel exhaust (derived from canola biodiesel or tallow biodiesel) and compared with control mice that were exposed to air or mineral diesel exhaust. Consistently with previous findings, the integrity of the BBB was significantly disrupted by exposure to mineral diesel exhaust. Tallow and canola biodiesel exhaust exposure resulted in no BBB disruption. Moreover, both tallow and canola biodiesels significantly attenuated oxidative stress in the brain. The data collectively suggest that biodiesel exhaust may exert significantly less detrimental effects on brain function, compared to mineral diesel.